An approach from charcoal analysis in geoarchaeological records to holocene vegetation dynamics in the semiarid lands of the central ebro basin (NE Spain) - Alcolea Gracia, Marta (2024)
Open-air archaeological sites in semiarid lands are overly infrequent causing a severe bias for the understanding of human settlement patterns. In the central Ebro basin (NE Spain) charcoal analysis conducted in off-site areas affected by recurrent human frequentation appear as adequate tools to understand climate biased and human-induced vegetation dynamics. In this work we present the study case of Jubierre (Los Monegros, NE Iberia) in the framework of a multidisciplinary project including archaeology, geomorphology and palaeobotany. An intense local-scale deforestation of woodlands would take place during the second part of the Holocene, inducing soil erosion episodes and ending in a degraded landscape with scarcely fertile and often bare soils. Charred plant macro-remains recovered from the slope deposits of isolated buttes and residual reliefs (tozales) have allowed suggest the existence of 3 different phases in relation to human settlement in the of junipers at a local-scale that probably corresponds with the pioneer forests which starred the postglacial forest reconquest. The second phase is revealing a local-scale retreat of junipers in parallel to the advance of Aleppo pine forests that could be related to the increase in anthropogenic disturbance in the area, during the Bronze Age (ca. 3500 cal BP). The last phase stars after an important data gap charcoal data are revealing the disappearance of the pine forests in parallel to the recovery of the juniper open landscapes probably due to depletion of lands.